2022
DOI: 10.1186/s13014-022-02079-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrafraction adaptation on PTV margins for MRI guided online adaptive radiotherapy for rectal cancer

Abstract: Purpose To determine PTV margins for intrafraction motion in MRI-guided online adaptive radiotherapy for rectal cancer and the potential benefit of performing a 2nd adaptation prior to irradiation. Methods Thirty patients with rectal cancer received radiotherapy on a 1.5 T MR-Linac. On T2-weighted images for adaptation (MRIadapt), verification prior to (MRIver) and after irradiation (MRIpost) of 5 treatment fractions per patient, the primary tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Traditional margin recipes such as the Van Herk formula may not be applicable for MRIgRT SBRT treatments due to the small number of fractions and the ability to utilize workflows which mitigate a portion of the intra-fraction motion, such as a baseline shift plan after an initial adaptive plan (28,30,40,41). Recently, Kensen et al proposed that PTV margins would be considered adequate for rectal MRIgRT patients at the point in which 95% of the primary GTV would receive the prescription dose in 90% of patients (42). Based on this definition, a 2 mm PTV margin expansion would be sufficient for all patients in our cohort as the minimum GTV coverage for all patients and delivered fractions was greater than or equal to 95%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional margin recipes such as the Van Herk formula may not be applicable for MRIgRT SBRT treatments due to the small number of fractions and the ability to utilize workflows which mitigate a portion of the intra-fraction motion, such as a baseline shift plan after an initial adaptive plan (28,30,40,41). Recently, Kensen et al proposed that PTV margins would be considered adequate for rectal MRIgRT patients at the point in which 95% of the primary GTV would receive the prescription dose in 90% of patients (42). Based on this definition, a 2 mm PTV margin expansion would be sufficient for all patients in our cohort as the minimum GTV coverage for all patients and delivered fractions was greater than or equal to 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kensen et al. proposed that PTV margins would be considered adequate for rectal MRIgRT patients at the point in which 95% of the primary GTV would receive the prescription dose in 90% of patients ( 42 ). Based on this definition, a 2 mm PTV margin expansion would be sufficient for all patients in our cohort as the minimum GTV coverage for all patients and delivered fractions was greater than or equal to 95%.…”
Section: Discussionmentioning
confidence: 99%
“…The choices for the penumbra and the cases used in this paper were made to be comparable to previous literature. The systematic and random standard deviations were chosen such that the resulting margins were within the range of margins reported for online adaptive radiotherapy 2-7 mm (de Bohoudi et al 2017, Winkel et al 2019, Muinck Keizer et al 2020, Intven et al 2021, Kensen et al 2022. As a consequence, the resulting considered systematic errors in the range 0-2 mm were relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] The integration of a linac within an MRI enables superior soft-tissue visualization during radiotherapy and can potentially facilitate the safe reduction of PTVs. 24,25 During these procedures, MRI-guidance may be used to gate the radiation delivery on either a predefined target window or extracardiac structures. 20,26 In a recent experimental study, we demonstrated that the dose delivery can be gated in a predefined cardiac phase in parallel with respiratory MLC-tracking based on real-time 2D cine MRI, which greatly reduced cardiorespiratory motion-induced dosimetric uncertainty.…”
Section: Introductionmentioning
confidence: 99%